Redesign of computerized decision support to improve antimicrobial prescribing - Baysari, Melissa T.; Del Gigante, Jessica; Moran, Maria; Sandaradura, Indy; Li, Ling; Richardson, Katrina L.; Sandhu, Anmol; Lehnbom, Elin C.; Westbrook, Johanna I.; Day, Richard O. (Applied Clinical Informatics, 2017)
Objective: To determine the impact of the introduction of new pre-written orders for antimicrobials in a computerized provider order entry (CPOE) system on 1) accuracy of documented indications for antimicrobials in the CPOE system, 2) appropriateness of antimicrobial prescribing, and 3) compliance with the hospital’s antimicrobial policy. Prescriber opinions of the new decision support were also explored to determine why the redesign was effective or ineffective in altering prescribing practices.Methods: The study comprised two parts: a controlled pre-post study and qualitative interviews. The intervention involved the redesign of pre-written orders for half the antimicrobials so that approved indications were incorporated into pre-written orders. 555 antimicrobials prescribed before (September – October, 2013) and 534 antimicrobials prescribed after (March – April, 2015) the intervention on all general wards of a hospital were audited by study pharmacists. Eleven prescribers participated in semi-structured interviews.Results: Redesign of computerized decision support did not result in more appropriate or compliant antimicrobial prescribing, nor did it improve accuracy of indication documentation in the CPOE system (Intervention antimicrobials: appropriateness 49% vs. 50%; compliance 44% vs. 42%; accuracy 58% vs. 38%; all p>0.05). Via our interviews with prescribers we identified five main reasons for this, primarily that indications entered into the CPOE system were not monitored or followed-up, and that the antimicrobial approval process did not align well with prescriber workflow.Conclusion: Redesign of pre-written orders to incorporate appropriate indications did not improve antimicrobial prescribing. Workarounds are likely when compliance with hospital policy creates additional work for prescribers or when system usability is poor. Implementation of IT, in the absence of support or follow-up, is unlikely to achieve all anticipated benefits.Citation: Baysari MT, Del Gigante J, Moran M, Sandaradura I, Li L, Richardson KL, Sandhu A, Lehnbom EC, Westbrook JI, Day RO. Redesign of computerized decision support to improve antimicrobial prescribing. Appl Clin Inform 2017; 8: 949–963 https://doi.org/10.4338/ACI2017042017040069
Keywords: Clinical decision support; Alerting; Order entry; Medication management; Hospital information systems